Implementing the immersed boundary method to solve for fluid-structure interaction - Jonathan, Wee (Nanyang Technological University, 2020)
Locomotion of many aquatic species is accomplished through the interaction of their bodies with surrounding fluid and driven by the contraction of muscles. This has attracted the interest of many engineers and researchers. Many numerical models and software have been developed over the years to solve for the locomotion of animals and the surrounding fluid, such as ANSYS Fluent and the immersed boundary (IB) method. In this study, the author determines the swimming trajectory of a modelled scallop and the flow field caused by the scallop locomotion by using IB method. The author first constructs a simplified geometry of a scallop model based on Amusium Balloti. Then, the beating pattern of the scallop is derived based on experimental observations. To do so, the author performs a fast Fourier transformation on the gape angle captured by experiments, and expresses the angle using Fourier series. Last, the time-dependent scallop trajectory and fluid motion are solved by using the Immersed Boundary Method Adaptive Mesh Refinement (IBAMR) infrastructure, which serves as an implementation of the IB method. The numerical model has shown that, first, the propulsion of water is located at the tip of the scallop. Second, the time-averaged motion of the swimming scallop is in the opposite direction as compared to that of the scallop in reality. This could be due to the fact that the scallop mantle, a soft tissue located around the edge of the scallop acts as a wall to channel out the fluid in its body, is not considered in this study. The author concludes that the scallop mantle plays a critical role in ensuring the swimming trajectory of the scallop is always intended and accurate, which should be taken into consideration in future studies.